Nancy’s nightmare - Dieringer, Suzanne, (SAGE business cases., 2022)
Nancy was a student who took an exam in her university's Testing Center because she needed extended time and a distraction-free environment. After she took the exam, she discovered that students who took the exam in the classroom accessed online resources to answer exam questions. This did not seem fair to Nancy, especially when she realized her score on the exam was significantly lower than that of friends who took the exam in the classroom. Nancy visited her professor and hoped they would notice the difference in exam scores and address the issue. Instead, the professor only offered suggestions to improve her performance. Nancy wondered if she should report the use of unauthorized materials to her professor or if she should take future exams in the classroom and have access to the same unauthorized materials her classmates did, even though that would violate the academic integrity policy of her university.